Evaluating post 2024 election scenarios for the UK based on political party manifestos. - Richard Stafford; Jenny Alexander; Stephen Axon; Zach Boakes; Elena Cantarello; Abigail R Croker; Marin Cvitanović; Victoria Dominguez Almela; Tilak Ginige; Natalie Harris; Ellie-Anne Jones; Yiannis Kountouris; et al. (PLoS ONE)
Manifestos provide a vision for political parties to enact if elected to government. While manifestos may not be enacted in full, they provide some of the best information for the public in deciding how to vote. However, manifestos tend to contain both enactable policies (e.g., tax cuts) and outcomes or visions of what these policies may achieve for society (e.g., higher disposal income). These outcomes may be deliberately misleading, inaccurate or only a partial picture of how policies will materialise, as it is unlikely a single policy will influence a single outcome. This work creates a complex system model of the economic, societal and environmental landscape of the UK and assesses how it would be affected if political parties enacted their 2024 general election manifesto policies in full. Our model creates a more complete picture of how the UK may look under different parties, rather than examining the manifestos alone (using data solely from manifestos almost 30% of our model's node values had no information, falling to just 5% after running the models).The model also has the capacity to provide a holistic reflection of the parties manifesto plans, illustrating the impacts each party's policies could have, should they be enacted. Prior to integrated analysis the most right-wing of the parties studied; Reform UK, aligned strongly with the Conservative party, however, post analysis Reform became a clear outlier. We also demonstrate unintended, misreported or indirect effects of policies. Most notably, parties who had the strongest tax cutting policies resulted in lower average incomes and higher levels of inequality in society, despite the rhetoric provided for these policies in the party manifestos. The results demonstrate the ability to integrate multiple types of information across political, economic, environmental, and social landscapes to help visualise implications of policy and politics more widely.